Contextualising religious education – Different understandings of teaching in Sami confirmation courses - Brydsten, Johan Runemark (HTS teologiese studies, 2020)
For the last 30 years, the Church of Sweden, along with other institutions, has offered special confirmation courses for the church’s young Sami members. The organisers and teachers involved with these Sami confirmation courses all stress the necessity of adapting their teaching to fit Sami contexts. Their views are supported by various steering documents, but the wording of these documents leaves room for differing interpretations, which has resulted in multiple understandings of what concrete adjustments should be implemented in the teaching.The overarching aim of this article is to analyse the differing views of how to adapt the teaching in Sami confirmation courses so as to better fit the Sami contexts. In particular, I examine whether these different views can be traced to differing understandings of what contextualising Religious Education entails.Ten interviews with people involved in teaching or organising the courses were analysed, along with archival material, using qualitative content analysis and theories regarding contextual theology, religious education and indigenous education.To capture these different theoretical perspectives, I suggest the concept of contextualised religious education and three central analytical questions: (1) ‘who is the teacher?’, (2) ‘how is the teaching organised?’ and (3) ‘what is the content of the teaching?’My in-depth analysis of the interviews and archival material, the sorting of the different views voiced in this material (based on the three questions above), together with inspiration from models of contextual theology, resulted in three new categories: dialogical contextual religious education, context-driven contextual religious education and faith-driven contextual religious education.